THE PREDOMINANT FACTORS THAT CONSIDERED BY FOREIGN STUDENTS IN CHOOSING HIGHER EDUCATION DESTINATION ABROAD - Nur Azureen Abd Hadi; Prof. Madya Dr. Mazuri Binti Abd. Ghani (International Journal of Accounting, Finance and Business, 2022)
The recruitment of students from the market is an extremely competitive endeavour for higher education institutions nowadays. In the meantime, Malaysia's higher education sector has seen growth during the last few decades. The growth is beneficial since Malaysia wants to be a centre for international education and is a popular study destination, especially for students from nearby and gulf nations. However, it is challenging to comprehend how international students choose higher education institutions given the abundance of institutions and courses available. Additionally, both public and private higher education institutions have been active and inventive in their use of marketing strategies and techniques to draw in and retain students as the competition for students grows. Even, higher education institution marketers contend that understanding the factors that influence applicants' decisions about colleges and academic programmes is essential to creating strong institutional positioning in the increasingly cutthroat higher education market. Moreover, the preference for developed nations, such as Malaysia, can be seen in the choice of study locations for international students. Thus, this paper tries to bring readers to understand what are other elements that influencing the international students’ destination choice for higher education.